High-gloss spraying-free reclaimed material PC / ASA alloy material as well as preparation method and application thereof

By adding recycled materials to high-gloss spray-free PC/ASA alloy material and adjusting the ratio, and adding silicone powder and compatible agent, the problem of poor material compatibility and dispersion is solved, and the effect of efficient use of recycled materials and improving the gloss and scratch resistance of the material is achieved.

CN119505508APending Publication Date: 2025-02-25SHANGHAI ZHONGLEI NEW MATERIAL SCI CO LTD

Patent Information

Application Number
CN202411840946.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing high-gloss spray-free PC/ASA alloy materials have poor compatibility and dispersion after adding silicon or fluorine materials, resulting in mist on the surface and cannot achieve high gloss. At the same time, the utilization rate of regenerated PC and regenerated ASA is not high, and there is a problem of poor stress resistance.

Method used

By adding a certain proportion of recycled materials to the PC/ASA alloy material raw materials, and adjusting the proportional relationship between recycled materials and non-recycled materials, it is possible to perform compounding; at the same time, silicone powder and compatible agent are added to improve the scratch resistance and gloss of the material.

Benefits of technology

It realizes efficient utilization of recycled materials, improves the mechanical properties and gloss of alloy materials, solves the problems of poor compatibility and dispersion, and improves the scratch resistance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187951120000021
    Figure BDA0005187951120000021
  • Figure BDA0005187951120000091
    Figure BDA0005187951120000091
  • Figure BDA0005187951120000101
    Figure BDA0005187951120000101
Patent Text Reader

Abstract

The invention relates to a high-gloss spraying-free reclaimed material PC / ASA alloy material as well as a preparation method and application thereof. The high-gloss spraying-free reclaimed material PC / ASA alloy material comprises the following raw material components in parts by weight: 20-50 parts of PC resin; 10 to 30 parts of ASA resin; 10 to 40 parts of regenerated PC resin; 20 to 35 parts of regenerated ASA resin; 5-10 parts of a compatilizer; 1-5 parts of silicone powder; 0.5 to 2 parts of carbon black; and 0.2-1 part of a dispersing aid. According to the PC / ASA alloy material and the preparation method thereof, the reclaimed material and the dispersing aid in a certain proportion are mixed into the raw materials of the PC / ASA alloy material for compounding, so that the prepared alloy material has excellent mechanical properties, the defect of performance reduction caused by the use of the reclaimed material is overcome, and efficient utilization of the reclaimed material is realized; and the compatilizer and the silicone powder are added into the raw materials of the PC / ASA alloy material, so that the prepared alloy material has excellent scratch resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-gloss spray-free recycled PC / ASA alloy material and a preparation method and application thereof. Background Art

[0002] PC / ASA alloy materials formed by graft copolymers of polycarbonate (PC) and acrylic rubber with acrylonitrile and styrene (ASA) have excellent mechanical and thermal properties and are widely used in the fields of automobiles, home appliances, and electronic and electrical materials. With the development of automobiles and electronic and electrical materials, high-gloss spray-free environmentally friendly materials will become a trend. The surface gloss of materials has become an important performance indicator of plastic products. The development of high-gloss PC / ASA alloy materials as electronic and electrical housing materials has been recognized by more and more manufacturers.

[0003] The usual method for preparing high-gloss spray-free PC / ASA alloy materials is to add silicon or fluorine materials to reduce the surface friction coefficient. However, after adding silicon or fluorine materials, the compatibility with the PC / ASA matrix material is poor, the dispersibility is poor, and the surface of the high-gloss spray-free PC / ASA material is foggy, but the high gloss effect is not achieved. Therefore, how to solve the problems of poor compatibility and poor dispersibility caused by scratch-resistant agents and improve the gloss of PC / ASA alloy materials is a technical difficulty that needs to be solved.

[0004] On the other hand, the utilization rate of recycled PC and recycled ASA in the existing technology is not high, and the recycled PC alloy material has the technical problem of poor stress resistance. Therefore, how to efficiently utilize recycled materials and overcome the performance degradation caused by the use of recycled materials is also a problem that is difficult to overcome in the existing technology. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-gloss spray-free recycled PC / ASA alloy material and its preparation method and application. The present invention designs the specific components of the raw materials of the high-gloss spray-free recycled PC / ASA alloy material. On the one hand, by adding a certain proportion of recycled materials to the raw materials of the PC / ASA alloy material, adjusting the ratio between the recycled materials and between the recycled materials and non-recycled materials, and further compounding with a dispersing aid, the prepared alloy material has excellent mechanical properties, overcomes the performance degradation caused by the use of recycled materials, and realizes the efficient utilization of recycled materials; on the other hand, by adding silicone powder and compatibilizer to the raw materials of the PC / ASA alloy material, the material obtains excellent scratch resistance, and also solves the problems of poor compatibility of the spray-free PC / ASA scratch resistance agent with the PC / ASA matrix material in the prior art, poor dispersibility, resulting in a decrease in its impact performance, and low gloss of the PC / ASA alloy material due to surface fogging.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a high-gloss spray-free recycled PC / ASA alloy material, wherein the high-gloss spray-free recycled PC / ASA alloy material comprises the following raw material components in parts by weight:

[0008]

[0009] On the one hand, the present invention mixes a certain proportion of recycled materials into the raw materials of PC / ASA alloy materials, and compounding with a dispersing aid, thereby overcoming the significant decline in performance caused by the use of recycled materials and realizing efficient utilization of recycled materials; on the other hand, the present invention adds a compatibilizer and silicone powder to the raw materials of PC / ASA alloy materials, so that the PC / ASA alloy materials have excellent scratch resistance, avoiding the problem of poor compatibility and dispersibility between the scratch resistance agent and the PC / ASA alloy materials, which leads to a decline in its impact performance, and the problem of low gloss of the PC / ASA alloy materials due to surface fogging.

[0010] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of PC resin can be 20 parts, 25 parts, 30 parts, 35 parts, 40 parts, 45 parts or 50 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0011] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of ASA resin can be 10 parts, 15 parts, 20 parts, 25 parts or 30 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0012] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of the recycled PC resin can be 10 parts, 15 parts, 20 parts, 25 parts, 30 parts, 35 parts or 40 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0013] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of the recycled ASA resin can be 20 parts, 22 parts, 25 parts, 27 parts, 30 parts, 32 parts or 35 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0014] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of the compatibilizer can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0015] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of silicone powder can be 1 part, 2 parts, 3 parts, 4 parts or 5 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0016] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of carbon black can be 0.5 parts, 0.75 parts, 1 parts, 1.25 parts, 1.5 parts, 1.75 parts or 2 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0017] In the present invention, in the raw material components of the high-gloss spray-free recycled PC / ASA alloy material, the weight proportion of the dispersing aid can be 0.2 parts, 0.4 parts, 0.6 parts, 0.8 parts or 1 parts, as well as specific point values ​​between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0019] Preferably, the ratio of the sum of the weight parts of the PC resin and the ASA resin to the sum of the weight parts of the recycled PC resin and the recycled ASA resin is 1:(0.25-1.5), more preferably 1:(0.75-1.5), for example, it can be 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.25 or 1:1.5.

[0020] In the present invention, by controlling the ratio of the sum of the weight fractions of non-recycled materials (PC resin and ASA resin) to the sum of the weight fractions of recycled materials (recycled PC resin and recycled ASA resin) within a specific range, a high-gloss spray-free recycled material PC / ASA alloy material with excellent performance is prepared. When the proportion of non-recycled materials is too small and the proportion of recycled materials is too large, the relevant mechanical properties of the high-gloss spray-free recycled material PC / ASA alloy material are significantly reduced and cannot meet the use requirements of the product; when the proportion of recycled materials is too small and the proportion of non-recycled materials is too large, the efficient use of recycled materials cannot be reflected.

[0021] Preferably, the weight ratio of the recycled PC resin to the recycled ASA resin is 1:(0.25-3), more preferably 1:(0.75-1.5), for example, it can be 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:1.75, 1:2, 1:2.25, 1:2.5, 1:2.75 or 1:3.

[0022] In the present invention, by controlling the weight ratio of recycled PC resin to recycled ASA resin within a specific range, a high-gloss spray-free recycled PC / ASA alloy material with excellent performance is prepared. When the weight ratio of recycled PC resin to recycled ASA resin is too large or too small, the mechanical properties of the alloy material are significantly reduced.

[0023] Preferably, the compatibilizer comprises MBS.

[0024] Preferably, the dispersing aid comprises vinyl bisstearamide and polytetrafluoroethylene.

[0025] Preferably, the mass ratio of the vinyl bisstearamide to polytetrafluoroethylene is 1:(0.5-2), for example, it can be 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:1.75 or 1:2.

[0026] Preferably, the high gloss spray-free recycled PC / ASA alloy material also includes 0.2-1 parts of antioxidants by weight, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, and 0.2-1 parts of ultraviolet absorbers, for example, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts.

[0027] Preferably, the antioxidant includes any one of aromatic amine antioxidants, hindered phenol antioxidants, and phosphite antioxidants, or a combination of at least two of them.

[0028] The antioxidant includes any one of antioxidant 168, antioxidant 1010, antioxidant 1098, antioxidant 626, antioxidant 1076, antioxidant 1098, antioxidant 3114, antioxidant 245, and antioxidant 618, or a combination of two or more thereof.

[0029] Preferably, the ultraviolet absorber includes any one of a benzoate ultraviolet absorber, a salicylate ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber, and a triazine ultraviolet absorber, or a combination of at least two of them.

[0030] The ultraviolet absorber includes any one or a combination of two or more of the ultraviolet absorber UV-O, ultraviolet absorber UV-9, ultraviolet absorber UV-531, ultraviolet absorber UV-P, ultraviolet absorber UV-234, ultraviolet absorber UV-326, ultraviolet absorber UV-327, ultraviolet absorber UV-328, ultraviolet absorber RMB, ultraviolet absorber UV-1164, ultraviolet absorber 3035, ultraviolet absorber triazine-5, ultraviolet absorber UV-1577, phenyl salicylate, 2-ethylhexyl salicylate, and light stabilizer HPT.

[0031] In a second aspect, the present invention provides a method for preparing the high-gloss spray-free recycled PC / ASA alloy material according to the first aspect, the method comprising the following steps:

[0032] The components of the high-gloss spray-free recycled PC / ASA alloy material are mixed in proportion and then melt-granulated to obtain the high-gloss spray-free recycled PC / ASA alloy material.

[0033] Preferably, the mixing time is 10-30 min, for example, 10 min, 15 min, 20 min, 25 min or 30 min.

[0034] Preferably, the melt granulation is to feed the mixed material into a twin-screw extruder, and obtain the PC / ASA alloy material after extrusion, drying and pelletizing.

[0035] Preferably, the temperatures of each zone of the twin-screw extruder are: zone one temperature is 225-235°C, zone two temperature is 235-245°C, zone three temperature is 245-255°C, zone four temperature is 260-270°C, zone five temperature is 260-270°C, zone six temperature is 260-270°C, zone seven temperature is 260-270°C, zone eight temperature is 255-265°C, zone nine temperature is 255-265°C, zone ten temperature is 255-265°C, and zone eleven temperature is 255-265°C.

[0036] Among them, 225-235℃ can be 225℃, 226℃, 228℃, 230℃, 232℃, 234℃ or 235℃, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0037] Among them, 235-245℃ can be 235℃, 236℃, 238℃, 240℃, 242℃, 244℃ or 245℃, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0038] Among them, 245-255℃ can be 245℃, 246℃, 248℃, 250℃, 252℃, 254℃ or 255℃, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0039] Among them, 260-270℃ can be 260℃, 262℃, 264℃, 265℃, 266℃, 268℃ or 270℃, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0040] Among them, 255-265℃ can be 255℃, 256℃, 258℃, 260℃, 262℃, 264℃ or 265℃, as well as specific point values ​​between the above point values. Due to limited space and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the said range.

[0041] Preferably, in step (2), the screw speed of the twin-screw extruder is 500-800 rpm, for example, 500 rpm, 550 rpm, 600 rpm, 650 rpm, 700 rpm, 750 rpm or 800 rpm.

[0042] Preferably, in step (2), the residence time of the mixture in the twin-screw extruder is 3 min to 5 min, for example, 3 min, 3.5 min, 4 min, 4.5 min or 5 min.

[0043] In a third aspect, the present invention provides an application of the high-gloss spray-free recycled PC / ASA alloy material according to the first aspect in automobile shell materials, household appliance shell materials and electronic and electrical appliance shell materials.

[0044] Compared with the prior art, the present invention has at least the following beneficial effects:

[0045] (1) The present invention mixes a certain proportion of recycled materials into the raw material components of the PC / ASA alloy material, adjusts the ratio between the recycled materials and between the recycled materials and the non-recycled materials, and compounding with a dispersing aid, so that the prepared alloy material has excellent mechanical properties, overcomes the performance degradation caused by the use of recycled materials, and realizes the efficient use of recycled materials.

[0046] (2) The present invention adds a certain proportion of compatibilizer and silicone powder to the raw material components of the PC / ASA alloy material, so that the PC / ASA alloy material has a certain scratch resistance and avoids the problem of poor compatibility and dispersibility between the scratch resistant agent and the PC / ASA alloy material, which leads to a decrease in its impact performance, and the problem of low gloss of the PC / ASA alloy material due to surface fogging. DETAILED DESCRIPTION

[0047] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0048] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0049] PC resin, PCL-1225Y, purchased from Teijin Group;

[0050] ASA resin, ASA957, purchased from Chi Mei Industrial;

[0051] Recycled PC resin, PC-08, was purchased from Guangzhou Boshang New Materials Co., Ltd.;

[0052] Recycled ASA resin, R-ASA, was purchased from Hailan Plastics;

[0053] Compatibilizer, MBS-E920, purchased from Arkema, France;

[0054] Silicone powder, RM4-7081, purchased from Dow Corning;

[0055] Carbon black, 930L, purchased from Orion;

[0056] Vinyl bisstearamide, Baomowei EBS-SF, purchased from KLKOLEO, Malaysia;

[0057] Polytetrafluoroethylene, DISP 30, was purchased from DuPont, USA;

[0058] Dispersing aid 1, the mass ratio of vinyl bisstearamide to polytetrafluoroethylene is 1:1;

[0059] Dispersing aid 2, the mass ratio of vinyl bisstearamide to polytetrafluoroethylene is 1:0.5;

[0060] Dispersing aid 3, the mass ratio of vinyl bisstearamide to polytetrafluoroethylene is 1:2;

[0061] Antioxidant 1, antioxidant 168, purchased from BASF;

[0062] Antioxidant 2, antioxidant 1010, purchased from BASF;

[0063] UV absorber 1 and UV absorber 234 were purchased from BASF;

[0064] UV absorber 2, UV absorber 3035, was purchased from BASF.

[0065] Example 1

[0066] A high-gloss spray-free recycled PC / ASA alloy material, the high-gloss spray-free recycled PC / ASA alloy material comprising the following components in parts by weight:

[0067]

[0068] The preparation method of the high gloss spray-free recycled PC / ASA alloy material is as follows:

[0069] (1) According to the above formula, PC resin, ASA resin, recycled PC resin, recycled ASA resin, compatibilizer, silicone powder, antioxidant, ultraviolet absorber and dispersing aid 1 are mixed in a high-speed mixer for the first time, and the mixing time is 5 minutes. After the first mixing is completed, 0.8 parts of carbon black is added for the second mixing, and the mixing time is 15 minutes to obtain a premix;

[0070] (2) Add the premix obtained in step (1) into a twin-screw extruder for melt co-extrusion, the extruder temperature: the temperature of zone 1 is 230°C, the temperature of zone 2 is 240°C, the temperature of zone 3 is 250°C, the temperature of zone 4 is 265°C, the temperature of zone 5 is 265°C, the temperature of zone 6 is 265°C, the temperature of zone 7 is 265°C, the temperature of zone 8 is 260°C, the temperature of zone 9 is 260°C, the temperature of zone 10 is 260°C, the temperature of zone 11 is 260°C, the extruder screw speed is 600 rpm, and the residence time is 3 min. After screw extrusion, cooling, drying, and pelletizing, a high-gloss spray-free recycled PC / ASA alloy material is obtained.

[0071] Examples 2-11, Comparative Examples 1-8

[0072] Examples 2-11 and Comparative Examples 1-8 respectively provide a high-gloss spray-free recycled PC / ASA alloy material and a preparation method thereof, which differ from Example 1 only in the types and / or amounts of components, as shown in Tables 1-3 (the amounts of each component in Tables 1-3 are all parts by weight), wherein “--” represents that the component is not added; the preparation method of the high-gloss spray-free recycled PC / ASA alloy material is the same as that of Example 1.

[0073] Table 1

[0074]

[0075]

[0076] Table 2

[0077]

[0078] Table 3

[0079]

[0080]

[0081] The performance of the high gloss spray-free recycled PC / ASA alloy material provided in the above examples and comparative examples was characterized, and the specific test method was as follows:

[0082] ASTM 3.2mm notched impact strength (J / m): Tested with reference to the test method of ASTM-D7136.

[0083] ISO tensile elongation at break (%): Tested according to the test method of ISO 527-1.

[0084] DIN flexural modulus (MPa): Tested in accordance with the ISO-178-2010 test method.

[0085] Blackness L value: measured with KONICA MINOLTA spectrophotometer CM-2500c.

[0086] Gloss 20° (GU) of high gloss color plate: measured by German BYK gloss meter.

[0087] Abrasion resistance gloss residual rate (%): Measured by German BYK scratch hardness tester and German BYK gloss meter, and expressed by [(gloss of color plate after test) / (gloss of color plate before test)]×100% measured by German BYK gloss meter before and after the material is scratched by German BYK scratch hardness tester.

[0088] The test data is shown in Table 4:

[0089] Table 4

[0090]

[0091]

[0092]

[0093] The test results show that:

[0094] (1) It can be seen from Examples 1 to 11 that the alloy material prepared by the present invention has excellent gloss and scratch resistance, and the degradation of mechanical properties caused by the use of recycled materials is overcome by compounding recycled materials with non-recycled materials and recycled materials in a certain proportion. The alloy material prepared according to Examples 1-7 has an ASTM 3.2mm notched impact strength (J / m) of 750-770J / m, a tensile elongation at break (%) of 75-80%, and a flexural modulus of 2050-2100MPa, and has excellent mechanical properties, realizing efficient utilization of recycled materials.

[0095] (2) It can be seen from Example 1 and Comparative Example 1 and Comparative Examples 4-6 that when the proportion of non-recycled materials in the raw materials is too small and the proportion of recycled materials is too large, and when there is no / lack of non-recycled materials in the raw materials, the relevant mechanical properties of the alloy material are significantly reduced and cannot meet the use requirements of the product.

[0096] (3) It can be seen from Example 1 and Comparative Examples 2-3 that when the mass ratio of the recycled PC resin to the recycled ASA resin is too large or too small, the mechanical properties of the obtained high-gloss spray-free recycled PC / ASA alloy material are significantly reduced.

[0097] (4) It can be seen from Comparative Examples 7-8 that the dispersing aid improves the blackness, gloss and mechanical properties of the material. When the raw material does not contain the dispersing aid, the gloss and wear resistance of the material are greatly reduced; when too much dispersing aid is added to the raw material, the mechanical properties of the alloy material will be reduced.

[0098] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high gloss spray-free recycled PC / ASA alloy material, characterized in that: The high gloss spray-free recycled PC / ASA alloy material comprises the following raw material components in parts by weight:

2. The high gloss spray-free recycled PC / ASA alloy material according to claim 1 is characterized in that: The ratio of the sum of the weight parts of the PC resin and the ASA resin to the sum of the weight parts of the recycled PC resin and the recycled ASA resin is 1:(0.25-2.5), and more preferably 1:(0.75-1.5).

3. The high gloss spray-free recycled PC / ASA alloy material according to claim 1 or 2, characterized in that: The weight ratio of the recycled PC resin to the recycled ASA resin is 1:(0.25-3), and more preferably 1:(0.75-1.5).

4. The high gloss spray-free recycled PC / ASA alloy material according to any one of claims 1 to 3, characterized in that: The compatibilizer includes MBS.

5. The high gloss spray-free recycled PC / ASA alloy material according to any one of claims 1 to 4, characterized in that: The dispersing aid includes a combination of vinyl bisstearamide and polytetrafluoroethylene; Preferably, the mass ratio of the vinyl bisstearamide to polytetrafluoroethylene is 1:(0.5-2).

6. The high gloss spray-free recycled PC / ASA alloy material according to any one of claims 1 to 5, characterized in that: The raw material components of the high gloss spray-free recycled PC / ASA alloy material also include 0.2-1 part of antioxidant and 0.2-1 part of ultraviolet absorber in parts by weight; Preferably, the antioxidant comprises any one or a combination of at least two of an aromatic amine antioxidant, a hindered phenol antioxidant or a phosphite antioxidant; Preferably, the ultraviolet absorber includes any one of a benzoate ultraviolet absorber, a salicylate ultraviolet absorber, a benzophenone ultraviolet absorber, a benzotriazole ultraviolet absorber or a triazine ultraviolet absorber, or a combination of at least two thereof.

7. A method for preparing the high gloss spray-free recycled PC / ASA alloy material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: The raw material components of the high-gloss spray-free recycled PC / ASA alloy material are mixed in proportion and then melt-granulated to obtain the high-gloss spray-free recycled PC / ASA alloy material.

8. The method according to claim 7, characterized in that The mixing time is 10-30min; Preferably, the melt granulation is to feed the mixed material into a twin-screw extruder, and after extrusion, drying and pelletizing, the high-gloss spray-free recycled PC / ASA alloy material is obtained.

9. The method according to claim 7 or 8, characterized in that: The temperatures of the zones of the twin-screw extruder are: zone 1 temperature is 225-235°C, zone 2 temperature is 235-245°C, zone 3 temperature is 245-255°C, zone 4 temperature is 260-270°C, zone 5 temperature is 260-270°C, zone 6 temperature is 260-270°C, zone 7 temperature is 260-270°C, zone 8 temperature is 255-265°C, zone 9 temperature is 255-265°C, zone 10 temperature is 255-265°C, and zone 11 temperature is 255-265°C; Preferably, the screw speed of the twin-screw extruder is 500-800 rpm; Preferably, the residence time of the mixed material in the twin-screw extruder is 3 min-5 min.

10. Use of the high-gloss spray-free recycled PC / ASA alloy material according to any one of claims 1 to 6 in automobile shell materials, household appliance shell materials and electronic and electrical appliance shell materials.

Citation Information

Patent Citations

  • Scratch-resistant high-gloss spraying-free PC / ASA alloy material and preparation method thereof

    CN105885379A

  • Phosphorus flame retardant standard sample in PC / ABS alloy material and preparation method of phosphorus flame retardant standard sample

    CN106832857A

  • Antibacterial PC / ASA alloy material and preparation method thereof

    CN107312301A

  • Halogen-free and flame-retardant polycarbonate alloy and preparation method thereof

    CN108117732A

  • Regenerated PC / ABS (polycarbonate / acrylonitrile-butadiene-styrene) material with wear-resistant, spray-free and low-gloss effects and preparation method

    CN116891626A

Cited By

  • PC / ASA alloy material and preparation method and application thereof

    CN121406108A

  • PC / ASA alloy material, preparation method and application thereof

    CN121406108B